2016
DOI: 10.1136/bmjqs-2016-005991
|View full text |Cite
|
Sign up to set email alerts
|

Our current approach to root cause analysis: is it contributing to our failure to improve patient safety?

Abstract: Background Despite over a decade of efforts to reduce the adverse event rate in healthcare, the rate has remained relatively unchanged. Root cause analysis (RCA) is a process used by hospitals in an attempt to reduce adverse event rates; however, the outputs of this process have not been well studied in healthcare. This study aimed to examine the types of solutions proposed in RCAs over an 8-year period at a major academic medical institution. Methods All state-reportable adverse events were gathered, and thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
222
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(227 citation statements)
references
References 28 publications
4
222
0
1
Order By: Relevance
“…Kellogg et al 7 report policy reinforcement among the most prevalent corrective actions stemming from RCAs. For example, after investigating a case in which a surgical sponge was left inside the patient, the RCA team concluded that the organisation's policy for counting equipment was effective and that human error was to blame.…”
Section: Aligning Corrective Actions To Causal Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kellogg et al 7 report policy reinforcement among the most prevalent corrective actions stemming from RCAs. For example, after investigating a case in which a surgical sponge was left inside the patient, the RCA team concluded that the organisation's policy for counting equipment was effective and that human error was to blame.…”
Section: Aligning Corrective Actions To Causal Factorsmentioning
confidence: 99%
“…Returning to the example highlighted by Kellogg et al ,7 the multiple cases of retained surgical sponges over the 8-year period raise the question: is counting not being performed well or does counting just not work well? Disguised observation can address the first option.…”
Section: Aligning Corrective Actions To Causal Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its popularity, whether RCA improves patient safety remains unclear . For example, a recent longitudinal mixed‐methods study investigating 302 RCAs during an eight‐year period showed that similar adverse events, such as retained foreign objects during surgery, recurred after RCA recommendations were implemented …”
Section: Discussionmentioning
confidence: 99%